SWOT Analysis of Development Strategy Entering the Disruption Era - maftuhah maftuhah; Siti Nurhasanah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2023)
AbstractThis study aims to find the right strategy for Darus Sunnah Pesantren to face in the disruption era. The disruption era is an era where digitalization is the motor of change that occurs in the social, economic, and cultural sectors. The strategy generated the strengths and weaknesses of Darus Sunnah Pesantren, as well as looking at opportunities and challenges outside Pesantren. This research is a qualitative type of case study model where interviews, observations, and document review as data collection techniques. The results showed that Pesantren Darus Sunnah could utilize its human resources, the majority of whom were millennials and had a good education, to take advantage of digital media, both to raise donations and market their books and promote the institution. Furthermore, based on existing strengths and threats, pesantren can empower their human resources by utilizing their alumni who are many in the digital world. Meanwhile, based on the weaknesses and opportunities, Darus Sunnah can take advantage of online donations and outside assistance to develop digital facilities and infrastructure within the Institution. Meanwhile, based on existing weaknesses and threats, Darus Sunnah can hold digital literacy programs and other programs that counteract the disruption era's negative impacts on stakeholders of Darus Sunnah Pesantren. This competency is also an additional competency for students in the era of disruption.AbstrakPenelitian ini bertujuan menemukan strategi yang tepat bagi Pesantren Darus Sunnah menghadapi era disrupsi. Era disrupsi merupakan era dimana digitalisasi menjadi motor perubahan yang terjadi dalam sektor sosial, ekonomi dan budaya. Strategi dihasilkan melalui analisis SWOT dengan menilai kekuatan dan kelemahan Pesantren Darus Sunnah, serta mencermati peluang dan tantangan di luar Pesantren. Penelitian ini berjenis kualitatif model studi kasus dimana wawancara, observasi dan telaah dokumen sebagai teknik pengumpulan data. Hasil penelitian menunjukan bahwa Pesantren Darus Sunnah dapat memanfaatkan sumber daya manusianya yang mayoritas dari kalangan milenial dan memiliki pendidikan baik untuk memanfaatkan media-media digital, baik untuk menggalang donasi, memasarkan karya tulis mereka dan mempromosikan Lembaga. Selanjutnya didasarkan pada kekuatan dan ancaman yang ada, pesantren dapat melakukan pemberdayaan sumber daya manusianya dengan memanfaatkan alumninya yang banyak berkecimpung di dunia digital. Sementara berdasarkan kelemahan dan peluang yang ada, Darus Sunnah dapat memanfaatkan donasi online dan bantuan-bantuan pihak luar untuk pengembangan sarana dan prasarana digital di dalam Lembaga. Sedangkan berdasarkan kelemahan dan ancaman yang ada, Darus sunnah bisa mengadakan program literasi digital dan program lain yang berfungsi menangkal dampak negatif dari era disrupsi bagi stakeholder Pesantren Darus Sunnah. Kompetensi ini sekaligus menjadi kompetensi tambahan bagi para santri di era disrupsi.How to Cite: Maftuhah., Nurhasanah, S. (2023). SWOT Analysis of Development Strategy Entering the Disruption Era. TARBIYA: Journal of Education in Muslim Society, 10(1), 13-38. doi:10.15408/tjems.v10i1. 33399.